Homeomorphisms of fuzzy topographic topological mapping (FTTM) - Ahmad, Tahir; Ahmad, Rashdi Shah; Liau, Li Yun; Zakaria, Fauziah; Wan Abd Rahman, Wan Eny Zarina (Department of Mathematics, FS, UTM, 2005)
The mathematical structure of a novel model for detecting the source of a magnetic field is presented. Simulation results show that the orientation of unbounded single current source can be determined with fairly accuracy. The model, FTTM, has the potential to be used for identifying the location of epileptic foci in epilepsy disorder patients.